Occipital Falcine Anaplastic Hemangiopericytoma Mimicking Meningioma - Davendran Kanesen (Journal of Neurosciences in Rural Practice, 2016)
The rarity of hemangiopericytoma (HPC) and its controversial histological classification result in its frequent misdiagnosis and thus make the treatment quite challenging. It is often difficult to distinguish these tumors from meningiomas based on clinical features and radiological findings. This is a case report of a man, diagnosed clinically and radiologically as meningioma, which turned out to be anaplastic HPC on histological examination. A 30-year-old man presented with 3 months of progressively worsening of headache and blurring of vision. Clinical examination revealed the right homonymous hemianopia with reduced visual acuity and papilledema bilaterally. Magnetic resonance imaging revealed a multilobulated and heterogenous extraaxial lesion attached to the occipital falx. It measured 9.0 cm (AP) × 5.5 cm (W) × 5.8 cm (CC) and expands bilaterally with major bulk on the left. An occipital craniotomy followed by a subtotal tumor excision was only achieved due to profuse bleeding intraoperatively. Histopathology confirmed an anaplastic HPC (WHO Grade 3). The importance of differentiation between HPCs and meningiomas cannot be overemphasized. A preoperative correct diagnosis is difficult, but it is important that it should be made. Multilobulated (mushroom appearance), prominent internal signal voids, relatively narrow dural attachment, and lytic destruction without calcifications are useful findings to distinguish HPCs from meningiomas.